The association of outdoor temperature with blood pressure, and its influence on future cardio-cerebrovascular disease risk in cold areas. Issue 6 (June 2020) - Yu, Bo; Jin, Shanshan; Wang, Chi; Yan, Shichun; Zhou, Xue; Cui, Xiaoming; Tang, Zhen; Luan, Qing; Guo, Yu; Bian, Zheng; Li, Liming; Chen, Zhengming; et al.
Abstract : Objectives: To explore whether lower outdoor temperature increases cardio-cerebrovascular disease risk through regulating blood pressure and whether indoor heating in winter is beneficial to prevent cardio-cerebrovascular disease in cold areas. Methods: We analyzed the data of 38 589 participants in Harbin from the China Kadoorie Biobank (CKB) during 2004–2008, with an average of 7.14-year follow-up. Linear regression analysis was performed to estimate the relationship between outdoor temperature and blood pressure. Cox regression analysis and logistic regression analysis were used to analyze the association of blood pressure with cardio-cerebrovascular event risk. Mediation analysis was performed to explore the role of blood pressure in the association between outdoor temperature and cardio-cerebrovascular events risk. Results: There was an increase of 6.7 mmHg in SBP and 2.1 mmHg in DBP for each 10 °C decrease in outdoor temperature when outdoor temperature was higher than 5 °C. There was an inverse association between outdoor temperature and cardio-cerebrovascular event morbidity. The increases in blood pressure and cardio-cerebrovascular event morbidity were attenuated in months when central heating was fully provided. Participants with hypertension have higher risks of cardio-cerebrovascular disease (hazard ratio 1.347; 95% CI 1.281–1.415), CVD (hazard ratio 1.347; 95% CI 1.282–1.416), MACE (hazard ratio 1.670; 95% CI 1.560–1.788) and stroke (hazard ratio 1.683; 95% CI 1.571–1.803). Mediation analysis demonstrated that the association between outdoor temperature and cardio-cerebrovascular events risk was potentially mediated by blood pressure. Conclusion: Temperature-driven blood pressure potentially mediates the association between outdoor temperature and cardio-cerebrovascular events risk. Indoor heating in winter is probably beneficial to cardio-cerebrovascular disease prevention by inhibition of blood pressure increase. Abstract : Supplemental Digital Content is available in the text